2017
DOI: 10.3136/fstr.23.525
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Synthesis of Phytosterol Linolenate Catalyzed by <i>Candida Rugosa</i> Lipase through Transesterification

Abstract: In recent years, phytosterols and their fatty acid esters have attracted much attention due to their beneficial effects on human health, while the latter showed excellent advantage in oil solubility. In this study, a novel method was developed for highly efficient synthesis of phytosterol linolenate through lipase-catalyzed transesterification of phytosterols with ethyl linolenate. The effects of lipase, and of solvents with different Log P values on the transesterification of phytosterols were investigated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…The esterification conversions were also high for most of the studies reviewed (Table 2), some of them reaching more than 95%, which is near to the conversions of chemical reactions. Low reaction times were found in those studies (Table 1), especially with C. rugosa lipase, with which many were lower than 2 h [65,78,84,86,88]. These results showed that the use of enzymes for the synthesis of phytosterol esters is very promising.…”
Section: General Aspectsmentioning
confidence: 92%
See 4 more Smart Citations
“…The esterification conversions were also high for most of the studies reviewed (Table 2), some of them reaching more than 95%, which is near to the conversions of chemical reactions. Low reaction times were found in those studies (Table 1), especially with C. rugosa lipase, with which many were lower than 2 h [65,78,84,86,88]. These results showed that the use of enzymes for the synthesis of phytosterol esters is very promising.…”
Section: General Aspectsmentioning
confidence: 92%
“…Phytosterols are insoluble in water, and their solubility in fats and oils is close to 1 g/100 g. To overcome this limitation, esterification of a fatty acid to the single hydroxyl of plant sterols has been studied as an approach to increase lipid solubility and facilitate food formulations [17]. For instance, He et al [65] reported that, by the esterification with linoleic acid, the solubility of phytosterols in oils was improved by 18 times. The esterification of phytosterols not only increases their solubility in oily solutions, but also decreases their melting point and improves flavor and bioavailability [66].…”
Section: Phytosterolsmentioning
confidence: 99%
See 3 more Smart Citations